Communication Management Strategy During Covid-19 in the Online Learning Process - Prietsaweny Riris T Simamora (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the communication management strategy in the learning process during the Covid-19 pandemic at Gajah Mada High School. The problem formulation in this article is (1) What is the communication management strategy in the learning process during the Covid-19 pandemic at Gajah Mada High School? (2) What are the results of the SWOT analysis of the communication management strategy in the learning process during the Covid-19 pandemic at Gajah Mada High School? This study uses a qualitative research method with interview, observation, and documentation techniques as well as a SWOT analysis at Gajah Mada High School. Informants from this study include the principal, vice principal for curriculum, and homeroom teachers. The results of this study are that Gajah Mada High School continues to use the same communication management as before the Covid-19 pandemic, namely online learning. Although there are several changes in the learning process, where the learning process that previously used face-to-face methods was changed to several methods to adjust to health protocols, including online methods, and so on